2004
DOI: 10.1074/jbc.m308938200
|View full text |Cite
|
Sign up to set email alerts
|

bcl-2 Induction of Urokinase Plasminogen Activator Receptor Expression in Human Cancer Cells through Sp1 Activation

Abstract: We have previously demonstrated that Bcl-2 overexpression in human breast carcinoma and melanoma cells synergizes with hypoxia to increase angiogenesis through up-regulation of vascular endothelial growth factor. In this work we demonstrated, for the first time, that Bcl-2 overexpression in cancer cells exposed to hypoxia modulates urokinase plasminogen activator receptor (uPAR) expression through Sp1 transcription factor and that the extracellular signal-regulated kinase (ERK) pathway plays a role in Sp1 tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
51
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 54 publications
5
51
0
Order By: Relevance
“…Our previous data demonstrate that Bcl-2 overexpression increases the expression of NF-kB and ERK 1/2, two molecules involved in the regulation of hTERT. 35,36 The Bcl-2 inhibitor HA14-1, although unable to inhibit the overall telomerase activity, altered intracellular hTERT protein localization, indicating that modulation of Bcl-2 function interferes with telomerase function by inducing nuclear export of hTERT. Recently, translocation of hTERT has been described as an additional mechanism for post-transcriptional regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous data demonstrate that Bcl-2 overexpression increases the expression of NF-kB and ERK 1/2, two molecules involved in the regulation of hTERT. 35,36 The Bcl-2 inhibitor HA14-1, although unable to inhibit the overall telomerase activity, altered intracellular hTERT protein localization, indicating that modulation of Bcl-2 function interferes with telomerase function by inducing nuclear export of hTERT. Recently, translocation of hTERT has been described as an additional mechanism for post-transcriptional regulation.…”
Section: Discussionmentioning
confidence: 99%
“…7-12 Although Sp1 regulates a number of oncogenes such as those coding for the vascular endothelial growth factor, urokinase plasminogen activator (uPA), uPA receptor, and epithelial growth factor receptor, [13][14][15] it also induces the expression of many tumor suppressor genes such as p27 kip1 , p21 WAF1/CIP1 , p16 INK4a , and pp2a-c. [16][17][18] In addition, the promoters of many proapoptotic genes have been found to contain Sp1-binding elements; for instance, fas, fas ligand, bax, and caspase 3.…”
Section: Uiccmentioning
confidence: 99%
“…Sp1 commonly undergoes posttranslational modifications such as phosphorylation, glycosylation, acetylation, ubiquitination, and sumoylation. [2][3][4][5][6] Numerous studies have documented that Sp1 activity and/or expression levels are elevated in human pancreatic cancer, breast cancer, colorectal cancer, gastric carcinoma, hepatocellular carcinoma, and thyroid carcinoma.7-12 Although Sp1 regulates a number of oncogenes such as those coding for the vascular endothelial growth factor, urokinase plasminogen activator (uPA), uPA receptor, and epithelial growth factor receptor, [13][14][15] it also induces the expression of many tumor suppressor genes such as p27 kip1 , p21 WAF1/CIP1 , p16 INK4a , and pp2a-c. [16][17][18] In addition, the promoters of many proapoptotic genes have been found to contain Sp1-binding elements; for instance, fas, fas ligand, bax, and caspase 3.19,20 Interestingly, it has been found that Sp1 can also induce the expression of many antiapoptotic genes (such as survivin, bcl-x, and bcl-w).20,21 Moreover, several recent studies have indicated that the overexpression of Sp1 causes apoptotic cell death in nontransforming cells, but the downregulation of the overexpressed Sp1 protein in human fibrosarcoma cell lines inhibits tumor formation. 13,22 Therefore, the effect of Sp1 overexpression on apoptosis regulation in transforming cells remains controversial, and the detailed mechanism of this process remains unclear.…”
mentioning
confidence: 99%
“…29,30 The signaling pathway involved in the expression of plasminogen activators and the respective inhibitors has been extensively studied. [31][32][33][34] However, the possible role of these pathways to mediate the effects of activated platelets on the plasminogen activation system by mesenchymal progenitors remains unknown. Most of the effects on the plasminogen activator system seem to involve mitogen-activated protein kinases (MAPK) such as extracellular signal-regulated kinase (ERK), c-Jun NH(2)-terminal kinase (JNK), and p38 as well as phosphatidylinositol 3-kinase (PI3K)/AKT pathways in other cells.…”
mentioning
confidence: 99%
“…Most of the effects on the plasminogen activator system seem to involve mitogen-activated protein kinases (MAPK) such as extracellular signal-regulated kinase (ERK), c-Jun NH(2)-terminal kinase (JNK), and p38 as well as phosphatidylinositol 3-kinase (PI3K)/AKT pathways in other cells. [31][32][33][34] Moreover, activated platelets were reported to enhance MAPK signaling in BMSC, suggesting a possible association with the plasminogen activation system of mesenchymal progenitors. progenitor cells.…”
mentioning
confidence: 99%